THE EFFECT OF MATHEMATIC LITERATION AND CRITICAL THINKING ABILITY ON MATHEMATICS PROBLEM-SOLVING ABILITY - Ratri Widianingsih; Uus Kusdinar (Universitas Ahmad Dahlan, 2019)
The repetition of SMA Negeri 4 Yogyakarta students shows that students' ability to solve mathematical problems is still low. This study aims to determine: (1) is there an effect of mathematical literacy on the ability to solve mathematics problems in class X State Senior High School (SMA Negeri) 4 Yogyakarta; (2) is there the effect of critical thinking on the ability of class X math problem-solving at SMA Negeri 4 Yogyakarta; (3) is there any effect of mathematical literacy and critical thinking on the ability of class X math problem-solving at SMA Negeri 4 Yogyakarta in the 2019/2020 school year. This research is a correlational quantitative associative study. This study's sample was students of class X MIPA 4 and X IPS 1 odd semester of SMA Negeri 4 Yogyakarta in 2019 / 2020. Data collection techniques were a breakdown test for mathematical literacy and problem-solving while a multiple-choice test for critical thinking questions. Research instrument test: validation test and reliability test. Analysis prerequisite test: normality test. Data analysis uses simple regression analysis, multiple regression, relative and effective contributions. Research instruments in the form of mathematical literacy questions, critical thinking, and problem-solving. This study's results indicate a positive influence of mathematical literacy and critical thinking together on the ability to solve problems with ð‘…x (1,2) ð‘¦ = 0.562, = 14.105, and the regression equation . However, the effect of mathematics literacy ability on the problem-solving ability of class X students of SMA Negeri 4 Yogyakarta is greater than the effect of critical thinking skills on class X students' problem-solving skills SMA Negeri 4 Yogyakarta.